Vaccine hesitancy in patients with solid tumors: a cross-sectional single-center survey - Angioletta Lasagna; Niccolò Alessio; Giulia Gambini; Catherine Klersy; Teresa Monaco; Salvatore Corallo; Daniela Cicognini; Paolo Pedrazzoli (BMC, 2024)
Abstract Background Vaccination rates are still suboptimal in cancer patients. Oncologists play a central role in recommending vaccines to their patients. Our goal was to investigate vaccine acceptance among cancer patients and understand the factors shaping their choices, thereby aiding physicians in better supporting their patients' vaccination decisions. Methods We designed a prospective cross-sectional survey exploring vaccination status, attitudes, and reasons for hesitancy towards vaccinations against the main vaccine preventable diseases (VPDs) among patients undergoing active cancer treatment. The primary endpoint was to evaluate the proportion of vaccinated subjects in our cohort of cancer patients. The secondary endpoints were to assess the proportion of vaccinated subjects against different types of VPDs: flu, COVID-19, pneumococcal disease, Herpes Zoster (HZ). Results Between 12 February and 01 March 2024, a total of three hundred and seventeen patients with cancer were invited to respond to the survey, 309 of whom (97%) agreed to do it. Two hundred seventy-three patients (0.88, 95% confidence interval [CI] 0.84-0.91) had received at least one vaccination. Two hundred thirty-one patients (74.76%) reported that at their first oncology visit their oncologist recommended vaccinations, primarily anti-flu (92.21%) and anti-SARS-CoV-2 (83.55%) vaccinations, while less frequently the anti-pneumococcal (42.42%) and anti-HZ (37%) vaccines were recommended. On the univariate analysis, age over 75 years (p = 0.041), marital status (p = 0.003) and the oncologist's vaccine recommendation during the first visit (p < 0.001) were significantly associated to vaccine acceptance. At the multivariable analysis, these variables were independently associated with vaccine willingness. Overall in our cancer population, the two main reasons for vaccine hesitancy were the lack of recommendation by the oncologist (55.41%, n = 128) and the lack of awareness of the importance of vaccination in the context of oncological care (49.35%, n = 114). Conclusions This survey emphasizes the importance of vaccine counseling by the oncologist to their patients. Oncologists can motivate patients to receive the correct vaccine schedule by addressing doubts and concerns about the potential negative impact of the vaccine on cancer and cancer therapies.